Perancangan Sistem Informasi Manajemen Berbasis Elektronikdi Posyandu Sejahtera 1 Kabupaten Blora - Santoso, Dian Budi, Ibnu Mardiyoko, SKM., MM, Arief Kurniawan Nur Prasetyo, SKM (2013)
Posyandu cadre burdened by administrative task to complete the reports besides their main duty to serve the community. Recapitulation of the data is still done manually so often cause human error in the process recently. Electronics based posyandu management information system that can perform data recapitulation automatically need to be develop so the occurrence of human error can be reduce. The purpose of this research is to design the electronic based management information system in Posyandu Sejahtera 1 Blora Regency. The research type is developmental research with prototyping approach. Subject of this research is the cadres of Posyandu Sejahtera 1 Blora Regency. Identification of the needs of the user and prototype development has been done in this research. Users explain that they accepted the prototype despite many shortcomings to be repaired.